Developing Karo Culture-Based Spiritual Intervention Model to Reduce HIV/AIDS Stigma - Elysabeth Sinulingga; Agung Waluyo; Sri Yona; Tris Yonado (Green Publisher Indonesia, 2022)
Introduction: People living with HIV/AIDS (PLWHA) experience various problems after being diagnosed with HIV, both physically and psychosocially. These problems cause PLWHA to close themselves so that they are not known to others because they feel stigmatised. This problem can cause PLWHA to continue stigmatising themselves and transmit HIV again to their partners or other people. This study aimed to develop a Karo culture-sensitive spiritual intervention model to prevent HIV stigma. Methods: Developing an intervention using the PATH (Problem – Analysis – Test – Help) method proposed by Buunk and Vugt (2008). Result: This model was developed based on cultural care theory and input from experts. Before the model development, the researcher had conducted preliminary studies both in qualitative and quantitative studies. The qualitative research established 14 themes, while the multivariant analysis found religiosity prevent HIV prevention dominantly. Conclusion: Developing a Karo culture-sensitive spiritual intervention model produces models, modules and pocketbooks in Karo culture-sensitive spiritual intervention to prevent HIV stigma.